Analysis of Pancasila Students Profile Media Needs for History Learning at Senior High School Number 1 in Indralaya - Umi Wulandari; Syarifuddin; Umi Chotimah; Sri Sumarni; Hermi Yanzi (Criksetra: Jurnal Pendidikan Sejarah, 2024)
Abstract:  In writing this article, the aim is to present the results of a needs analysis related to the use of media containing the profile character of Pancasila students by distributing questionnaires and interviews directly to the research location. This research was conducted at Senior High School Number 1 in 1 Indralaya using descriptive qualitative research methods. The data obtained in this research is in the form of qualitative data with analysis of the data obtained before being compiled into descriptive data for use in writing. Data collection techniques use questionnaires distributed to students and interviews conducted with educators. The research results obtained show that in the learning process students are more interested in learning that uses internet technology. The use of the internet in the history learning process has not been widely implemented in every school. In applying the dimensions of the Pancasila student profile, the internet can be an alternative by producing various media. This media can be used in the learning process through interesting history lessons. The media produced is in the form of posters, videos and historical dominoes. Abstrak: Dalam kepenulisan artikel ini memiliki tujuan untuk mengemukakan mengenai hasil dari analisis kebutuhan terkait penggunaan media bermuatan karakter profil pelajar Pancasila dengan penyebaran angket dan wawancara langsung ke lokasi penelitian. Penelitian ini dilakukan di SMA Negeri 1 Indralaya dengan menggunakan metode penelitian deskriptif kualitatif. Data yang diperoleh dalam penelitian ini berbentuk data kualitatif dengan dilakukan analisis terhadap data yang diperoleh sebelum disusun menjadi data deskriptif untuk digunakan dalam tulisan. Teknik pengumpulan data menggunakan angket yang dibagikan kepada peserta didik dan wawancara dilakukan bersama pendidik. Hasil penelitian yang diperoleh menunjukkan bahwa dalam proses pembelajaran  peserta didik lebih tertarik dengan pembelajaran yang menggunakan teknologi internet. Penggunaan internet dalam proses pembelajaran sejarah belum banyak diterapkan dalam setiap sekolah. Dalam penerapan dimensi profil pelajar Pancasila, internet dapat menjadi salah satu alternatif dengan menghasilkan berbagai media. Media tersebut bisa digunakan dalam proses pembelajaran melalui pembelajaran sejarah yang dibuat secara menarik. Media yang dihasilkan berupa poster, video dan domino sejarah.